PHYSICAL AND SENSORY CHARACTERISTICS OF CHICKEN NUGGETS WITH UTILIZATION RICE BRAN TO SUBSTITUTE WHEAT FLOUR - C Maliluan; Y B Pramono; B Dwiloka (Jurnal Aplikasi Teknologi Pangan, 2013)
The purpose of this research is to create a product with a good characteristic both physical and sensory. The variables in this research is texture, Water Holding Capacity, and sensory test. The texture analysis was carried out by Texture Analyzer,  The analysis of  Water Holding Capacity were performed according to the Hamm. The statictical design of the research is Completely Randomized Design (CRD) with 5 treatments and 4 replications. In the formulation, rice bran was used as a source of dietary fiber to replaced wheat flour at five different levels i.e. 0% (Control), 25% (Treatment 1), 50% (Treatment 2), 75%       (Treatment 3), and 100% (Treatment 4). The data of physical charateristic from the randomized design were analysed by analisis of variance. Based on the results of the study showed that the use of rice bran significantly (P <0.05) increased texture and decreased WHC. Overall, utilization rice bran as a substitute for wheat flour lower the physical properties and sensory of chicken nuggets.